Causal links between serum micronutrients and epilepsy: a Mendelian randomization analysis - Chen, Haohao; Zheng, Zequn; Cai, Xiaorui; Gao, Fenfei (Frontiers in Neurology, 2024)
Background: Micronutrient levels play a critical role in epilepsy. This study investigates the impact of micronutrient levels on epilepsy via Mendelian randomization (MR).Methods: A two-sample MR framework evaluated the genetic association between fifteen serum micronutrients and epilepsy phenotypes. The analysis included calcium, iron, Zinc, selenium, copper, magnesium, potassium, folate, vitamins B6, B12, C, D, E, retinol, and carotene against all epilepsy, generalized epilepsy, childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy (JME), generalized tonic-clonic seizures alone and with spike-wave electroencephalography (GTCS), and various focal epilepsy phenotypes (with hippocampal sclerosis (HS), lesions other than HS, lesion-negative). The random-effects inverse-variance weighted (IVW) model was the primary method used, supported by heterogeneity and pleiotropy assessments.Multivariable Mendelian randomization analyses (MVMR) were used to identify micronutrients that are significantly causally associated with different epilepsy subtypes and to confirm the most potential causal risk factors for these subtypes.Results: Zinc conferred an increased risk of focal epilepsy with HS (OR = 1.01; P = 0.045). Carotene was similarly linked to higher risks of lesion-negative cases (OR = 1.129; P = 0.037). Conversely, vitamin B6 was associated with reduced risks of focal epilepsy with HS (OR = 0.949; P = 0.020), and vitamin D was linked to decreased risks of both CAE (OR = 0.976, 95% CI: 0.959-0.993, P = 0.006) and JAE (OR = 0.986, 95% CI: 0.973-0.999, P = 0.032). These associations were robust, showing minimal heterogeneity and no evidence of pleiotropy across various sensitivity analyses. After adjustment using MVMR, significant causal relationships between vitamin D and both CAE and JAE remained.Furthermore, the causal relationship between zinc and vitamin B6 on focal epilepsy with HS became nonsignificant, while carotene shifted from a risk factor to a protective factor for focal epilepsy lesionnegative after adjusting for vitamin D.Conclusions: MR estimates provide robust evidence for the causal effects of vitamin B6 and D on reducing the risk of focal epilepsy with HS, CAE, and JAE, which might provide alternative treatment strategies.